Dreamz Florist Enterprise / Suhaida Mohd Sobri ... [et al.] - Mohd Sobri, Suhaida; Zakaria, Zamrosmiza; Mohd Radzuan, Sharina; Ariffin, Noor Arni; Mohamad Hamdan, Norhana (2001)
DREAMZ FLORIST ENTERPRISE has it's own administration. It is important part in making a business plan. It is all about the administration of the business and it can show us the skillful entrepreneur in managing and administrating the business. It also tells us about the mission and then the objective of the business plan that has been planned. The mission and the objective are made in order to make sure that the business more dynamics where it can make all the demanded of the customer can be filled. The administrative also want to make sure that the management of the business can be run smoothly. The administrative is very important and it is clearly, orderly, easy to understand and being fulfilled with the responsibility of the entrepreneur to the business. It also prepared all the budgeted that involved in the administration of the business.